Characterization of the comparative drug binding to intra- (liver fatty acid binding protein) and extra- (human serum albumin) cellular proteins. (October 2015) - Rowland, Andrew; Hallifax, David; Nussio, Matthew R.; Shapter, Joseph G.; Mackenzie, Peter I.; Brian Houston, J.; Knights, Kathleen M.; Miners, John O.
Abstract 1. This study compared the extent, affinity, and kinetics of drug binding to human serum albumin (HSA) and liver fatty acid binding protein (LFABP) using ultrafiltration and surface plasmon resonance (SPR). 2. Binding of basic and neutral drugs to both HSA and LFABP was typically negligible. Binding of acidic drugs ranged from minor (fu > 0.8) to extensive (fu < 0.1). Of the compounds screened, the highest binding to both HSA and LFABP was observed for the acidic drugs torsemide and sulfinpyrazone, and for β-estradiol (a polar, neutral compound). 3. The extent of binding of acidic drugs to HSA was up to 40% greater than binding to LFABP. SPR experiments demonstrated comparable kinetics and affinity for the binding of representative acidic drugs (naproxen, sulfinpyrazone, and torsemide) to HSA and LFABP. 4. Simulations based on in vitro kinetic constants derived from SPR experiments and a rapid equilibrium model were undertaken to examine the impact of binding characteristics on compartmental drug distribution. Simulations provided mechanistic confirmation that equilibration of intracellular unbound drug with the extracellular unbound drug is attained rapidly in the absence of active transport mechanisms for drugs bound moderately or extensively to HSA and LFABP.